Induction of ferroptosis by natural products in non-small cell lung cancer: a comprehensive systematic review - Zhang, Qiang; Xia, Yuting; Wang, Feiyan; Yang, Dongfeng; Liang, Zongsuo (Frontiers in Pharmacology, 2024)
Lung cancer is one of the leading causes of cancer-related deaths worldwide that presents a substantial peril to human health. Non-Small Cell Lung Cancer (NSCLC) is a main subtype of lung cancer with heightened metastasis and invasion ability. The predominant treatment approaches currently comprise surgical interventions, chemotherapy regimens, and radiotherapeutic procedures.However, it poses significant clinical challenges due to its tumor heterogeneity and drug resistance, resulting in diminished patient survival rates. Therefore, the development of novel treatment strategies for NSCLC is necessary. Ferroptosis was characterized by iron-dependent lipid peroxidation and the accumulation of lipid reactive oxygen species (ROS), leading to oxidative damage of cells and eventually cell death. An increasing number of studies have found that exploiting the induction of ferroptosis may be a potential therapeutic approach in NSCLC. Recent investigations have underscored the remarkable potential of natural products in the cancer treatment, owing to their potent activity and high safety profiles. Notably, accumulating evidences have shown that targeting ferroptosis through natural compounds as a novel strategy for combating NSCLC holds considerable promise. Nevertheless, the existing literature on comprehensive reviews elucidating the role of natural products inducing the ferroptosis for NSCLC therapy remains relatively sparse. In order to furnish a valuable reference and support for the identification of natural products inducing ferroptosis in anti-NSCLC therapeutics, this article provided a comprehensive review explaining the mechanisms by which natural products selectively target ferroptosis and modulate the pathogenesis of NSCLC.